Integrating Gender into the Climate-Smart Village Approach of Scaling out Adaptation Options in Agriculture - Chanana, Nitya; Khatri-Chhetri, Arun; Pande, Kunal; Joshi, Rajashree (2018)
As a step towards building climate resilience, a USAID funded project aimed at scaling out climate-smart agriculture through the CSV approach in Madhya Pradesh in India, is providing an enabling platform to women farmers to manage and lead climate change adaptation and mitigation interventions in their villages. This info note presents preliminary information on each of the major steps of a CSV approach and its components and linking them with gender and CSA. It focuses on the initial findings of a baseline assessment, the process of CSV formation and the initial output of CSA implementation (for Rabi/monsoon season) with due consideration of gender dynamics in agriculture.